For the „high performers“ and „us Austrians“: A media discourse analysis of social policy reforms of the ÖVP/FPÖ government 2017-2019 in Austria - Griesser, Markus; Beyer, Karl; Pühringer, Stephan (Momentum Quarterly, 2024)
When inaugurated in December 2017, the ÖVP/FPÖ coalition in Austria presented far-reaching plans for reforming social policies and the labour market in its government programme. While many of these plans failed due to the early collapse of the coalition in May 2019 others have been adopted. This article will focus on two of these reforms, namely regarding working hours policy and social assistance policy. More precisely, we ask in a comparative perspective on policies which discursive frames or frames of interpretation played a role in media discussions about the reforms mentioned. We examine the media discussions on the basis of three Austrian daily newspapers and with the help of a specific discourse-analytical approach. This suggests that the discursive framing in the two policy fields is characterized by far-reaching differences. We interpret these differences against the background of debates in political science regarding the social and labour market policy profile of so-called Populist Radical Right Parties when entering a coalition with conservative parties.
Keywords: Populist Radical Right Parties; Neoliberalism; Social and labour market policy; Interpretive Policy Analysis; Critical Discourse Analysis